2014
DOI: 10.1186/2193-1801-3-570
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual function after transobturator tape in women with urodynamic stress urinary incontinence

Abstract: We evaluate quality of life and sexual function before and after transobturator tape procedure (TOT) using the International Consultation on Incontinence Questionnaire (ICIQ -SF) and Female Sexual Function Index (FSFI). Between 2008 and 2013, 92 patients with stress urinary incontinence (SUI) underwent TOT procedure. A total of 81 patients were sexual active and enrolled in the study. All patients completed the Turkish translation ICIQ -SF and FSFI forms before and 1, 3, 6, 12 months after surgery. To evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
14
4
Order By: Relevance
“…In this study, they showed that sexual dysfunction in premenopausal women was related to personal distress. Simsek et al [7] did not observe any significant difference in the total FSFI scores of premenopausal and postmenopausal women, although the scores of premenopausal women were higher. In our study, there was no significant difference in the preoperative FSFI scores between the premenopausal and postmenopausal women; however, in the postoperative 6 and 12 months, FSFI scores were significantly higher in the premenopausal group when compared with the scores of the postmenopausal group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, they showed that sexual dysfunction in premenopausal women was related to personal distress. Simsek et al [7] did not observe any significant difference in the total FSFI scores of premenopausal and postmenopausal women, although the scores of premenopausal women were higher. In our study, there was no significant difference in the preoperative FSFI scores between the premenopausal and postmenopausal women; however, in the postoperative 6 and 12 months, FSFI scores were significantly higher in the premenopausal group when compared with the scores of the postmenopausal group.…”
Section: Discussionmentioning
confidence: 99%
“…Simsek et al [7] evaluated the effect of TOT on sexual functions in 81 women with FSFI in their study with one-year follow-up. There was significant improvement in sexual functions in FSFI total scores and all domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, urinary disturbances based on the Incontinence Questionnaire-Urinary Incontinence Short Form and clinical examination such as urinary frequency, incontinence, and feeling of incomplete emptying were evaluated before and after the treatment [30][31][32]. A positive response was mainly considered as an improvement in motor function, urinary symptoms, and neurologic signs.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…When preoperative and postoperative FSFI scores were compared, total scores elevated in non-complicated patients whereas these scores did not elevate in complicated patients. When post-surgery FSFI scores of both groups were compared, scores of complicated patients clearly went down and the difference was found to statistically be significant (19).…”
Section: Comparing Fsfi Resultsmentioning
confidence: 95%